How to finance the European Union's building decarbonisation plan - Ugnė Keliauskaitė; Ben McWilliams; Giovanni Sgaravatti; Simone Tagliapietra (Bruegel, 2024)
By 2030, the European Union must reduce emissions from the heating and cooling of buildings - responsible for 13 percent of EU emissions - by the equivalent of the annual emissions of Slovakia. This requires a near tripling of the current decarbonisation rate. But the time gap between high upfront costs and long-term payback from renovation works deter consumers from investing in energy renovation. To address these challenges, the EU has introduced a policy toolkit that includes strengthened price signals against fossil-fuel heating through emissions trading, and setting energy-consumption reduction targets in the Energy Performance Building Directive (EPBD). EU countries must take the EPBD targets seriously and implement policies to accelerate building retrofits and the adoption of clean heating. If they don't, there is a risk that EU climate targets will not be met, and the costs for households of subjecting domestic heating to emissions trading could be almost twice the higher costs seen during the 2022 energy crisis. We estimate that achieving the EPBD's energy savings targets requires filling an investment gap of about exteuro150 billion per year up to 2030. This is a daunting but feasible goal. By leveraging energy savings from electrification and retrofitting to reduce renovation costs, the investment gap could be more than halved. Additionally, effective use of EU funds and emissions trading revenues will further shrink the gap. A mix of grants, preferential loans and obligations is needed, as no single policy will speed up energy renovations. Prioritising grants for the worst-performing buildings, often occupied by vulnerable consumers, will yield climate benefits and benefits in terms of improved air quality, health, productivity, energy security and lower future government outlays to alleviate energy poverty. Traditional public subsidies have not successfully engaged the banking sector, which now must help to foster private-public financing mechanisms. Countries also need to adjust relative energy prices for heating through taxation and subsidies, and expand one-stop-shops to streamline the renovation process for consumers.
Keywords: 330; European Green Deal; climate change; eu governance